Ion Conduction in a Semicrystalline Polyviologen and Its Polyether Mixtures. Issue 3 (10th November 2014) - Lee, Minjae; Choi, U Hyeok; Colby, Ralph H.; Gibson, Harry W.
<x xml:space="preserve">Abstract</x> Polyviologen (PV) with C6 spacers and bis(trifluoromethylsulfonyl)imide (Tf2N−) anions is a semicrystalline polymer. Its semicrystalline mixtures with 18‐crown‐6 (18C6), 30‐crown‐10 (30C10), dibenzo‐30‐crown‐10 (DB30C10), and poly(ethylene glycol) dimethyl ether 1000 (PEGDME) are prepared by evaporation of solutions. The ionic conductivities, measured by dielectric relaxation spectroscopy, of all of the mixtures are 10–100× higher than that of PV itself in spite of the fact that the ionic contents are reduced by ≈25%. The room temperature (RT) ionic conductivity of PV is 1.1 × 10−9 S cm−1, and that of its mixture with DB30C10 is over 100‐fold higher even though its Tg is slightly above that of PV. The mixtures with 30C10 and PEGDME have similar RT conductivities. However, the 18C6 mixture, in spite of a 9 °C drop in Tg, displays a room temperature (RT) conductivity 10× lower than the other mixtures. Although plasticization probably plays a role, complexation of the polyethers with the viologen units plays a role in the higher conductivities, it is believed, because it increases the fraction of non‐ion‐paired mobile anions. With 30C10 and DB30C10, polypseudorotaxane formation is envisioned to play a significant role in conductivity enhancement. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>